Effect of 24 h glucose fluctuations on 30-day and 1-year mortality in patients with acute myocardial infarction: an analysis from the MIMIC-III database - Liu, Xiaohe; Zhang, Guihong; Li, Dan; Ruan, Zhishen; Wu, Bo (Frontiers in Cardiovascular Medicine, 2024)
It is recognized that patients' blood glucose fluctuates over time during acute disease episodes, especially during the outbreak of cardiovascular events, regardless of the presence of an abnormal blood glucose profile prior to admission to the hospital.Glucose fluctuations in patients with acute myocardial infarction (AMI) in the intensive care unit (ICU) are currently not adequately monitored and studied. We focused on blood glucose fluctuation values within 24 hours of admission to assess their association with 30-day and 1-year mortality.Data of patients with AMI aged 18 years or older from the Critical Care Medical Information Marketplace database III V1.4 were available for analysis in this research.Glucose data were obtained by measurement. A total of 390 of them were treated with PCI. The principal consequence was 30-day and 1-year mortality in patients with AMI.The effect of different glucose fluctuations within 24 hours of admission on mortality was predicted by constructing a multivariate Cox regression model with four model adjustments and Kaplan-Meier survival curves. Additionally, we performed curve-fitting analyses to show the correlation between blood glucose fluctuations and risk of death.We selected 1699 AMI patients into our study through screening. The included population was categorized into three groups based on the tertiles of blood glucose fluctuation values within 24 hours of admission to the ICU. The three groups were <25mg/dl, 25-88mg/dl and >88mg/dl. By cox regression analysis, the group with the highest blood glucose fluctuation values (>88 mg/dl) had the most significant increase in 30-day and 1-year mortality after excluding confounding factors (30-day mortality adjusted HR=2.11; 95% CI = 1.49-2.98 p<0.001; 1-year mortality adjusted HR=1.83; 95% CI = 1.40-2.39 p<0.001). As demonstrated by the Kaplan-Meier survival curves, the group with the greatest fluctuations in blood glucose has the worst 30-day and 1-year prognosis.The extent of glucose fluctuations in patients with AMI in the first 24 hours after ICU admission is an essential predictor as to 30-day as well as 1-year mortality. When blood glucose fluctuates more than 88 mg/dl within 24 hours, mortality increases significantly with the range of blood glucose fluctuations.